Research on the high-performance transmission control protocol under lossy networks - Kai PAN; Hui LI (Tongxin xuebao)
A novel redundancy parameter updating algorithm based on network coding combined TCP was proposed.Reduced coefficients linear network coding which could simplify decoding and simultaneously reduce the overhead in the header was involved in encoding process before data transmission.During the simulations,NS2 was used to test the communication under different lossy networks.Results showed that the new protocol which adopted this algorithm re-tained the fairness and outperformed the other protocols in effectiveness and adaptability especially under light-load net-works.